2012
DOI: 10.1002/rcm.6204
|View full text |Cite
|
Sign up to set email alerts
|

Determination of isotopic labeling of proteins by precursor ion scanning liquid chromatography/tandem mass spectrometry of derivatized amino acids applied to nuclear magnetic resonance studies

Abstract: This method is ideally suited for assessing the extent of protein labeling prior to NMR studies, where the isotopic labeling is a determining factor in the quality of resulting protein spectra, and can be applied to a multitude of different biological samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Using our in situ RE values and mussel growth (shell and tissue) data, such simulations imply that PPP could account for approximately 20 % of mussel growth during the postspring bloom period. This result is also consistent with reports that M. edulis can assimilate PPP, as recently demonstrated by the use of isotopically labelled PPP (Leblanc et al 2012). The main difference between Rosland's and Saraiva's parameters is related to the different predictions for reproductive behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…Using our in situ RE values and mussel growth (shell and tissue) data, such simulations imply that PPP could account for approximately 20 % of mussel growth during the postspring bloom period. This result is also consistent with reports that M. edulis can assimilate PPP, as recently demonstrated by the use of isotopically labelled PPP (Leblanc et al 2012). The main difference between Rosland's and Saraiva's parameters is related to the different predictions for reproductive behaviour.…”
Section: Discussionsupporting
confidence: 93%
“…Assimilation of microalgae was determined through the analyses of isotopic labeling levels of fatty acids (FA) in the food (picoplankton culture) and in the larvae fed with these species 64 65 . Samples were lyophilized, weighed and lipids extracted by a modified Folch procedure 66 as described in Parrish et al .…”
Section: Methodsmentioning
confidence: 99%
“…The calculation of the percentage of isotope label for a given fatty acid is based on the ratio of the peak area of each isotopomer relative to the sum of all possible isotopomer signals using similar calculation method developed by Leblanc et al . for amino acids 65 .…”
Section: Methodsmentioning
confidence: 99%
“…Together, these results suggest a diatom-dominated spring bloom (Irigoien 2000(Irigoien , M enet-N ed elec et al 2013. Considering the size fraction analyzed in this study (<20 µm), it is likely that diatoms contributing to the spring bloom originate either from nanoplanktonic diatoms or broken parts of bigger diatoms from an earlier bloom (LeBlanc et al 2012). Surprisingly, the total FA concentration measured on this date was the lowest reported during the sampled v www.esajournals.org Fig.…”
Section: Pelagic Vs Benthic Trophic Source Dynamicsmentioning
confidence: 66%
“…Interestingly, picoeucaryotes were the same settlement trigger for Mytilidae larvae in the present study as had been observed by Toupoint et al (2012a), who focused on M. edulis larvae in a coastal oligotrophic lagoon. Adult mussels and oysters are able to retain picophytoplankton cells and assimilate their carbon (LeBlanc et al 2012, Sonier et al 2017, Rahman et al 2020. Energetic modeling indicates that picophytoplankton could contribute from 14% to 29% of the energy needed to support adult mussel growth during the postspring bloom period (Sonier et al 2016).…”
Section: Trophic Settlement Triggermentioning
confidence: 99%